2007
DOI: 10.2337/db06-1258
|View full text |Cite
|
Sign up to set email alerts
|

Implantation Site–Dependent Dysfunction of Transplanted Pancreatic Islets

Abstract: OBJECTIVE-Clinical islet transplantations are performed through infusion of islets via the portal vein into the liver. This study aimed at characterizing the influence of the implantation microenvironment on islet graft metabolism and function.RESEARCH DESIGN AND METHODS-Islets were transplanted into their normal environment, i.e., the pancreas, or intraportally into the liver of mice. One month posttransplantation, the transplanted islets were retrieved and investigated for changes in function and gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 33 publications
2
61
1
Order By: Relevance
“…This argues for the importance of finding an alternate nonhepatic site that will not interfere with full glucagon responses to hypoglycemia. Recently, additional metabolic defects in intrahepatically transplanted islets involving insulin synthesis, insulin secretion, and glucose oxidation have been reported (15). One study reported that ␣-cell responses to mild non-insulin-induced hypoglycemia (80 Ϯ 3 mg/dl) in dogs were subnormal (16).…”
Section: Discussionmentioning
confidence: 99%
“…This argues for the importance of finding an alternate nonhepatic site that will not interfere with full glucagon responses to hypoglycemia. Recently, additional metabolic defects in intrahepatically transplanted islets involving insulin synthesis, insulin secretion, and glucose oxidation have been reported (15). One study reported that ␣-cell responses to mild non-insulin-induced hypoglycemia (80 Ϯ 3 mg/dl) in dogs were subnormal (16).…”
Section: Discussionmentioning
confidence: 99%
“…The main non-endocrine component consists of duct cells [2,10] that might be considered as potential inducers and active participants in local inflammatory and immune reactions, given their expression of tissue factor [11], CD40 [12] and MHC-II antigens [13], and their production of cytokines and nitric oxide [14,15]. The duct cell contamination of human islet cell grafts could make them particularly vulnerable after injection into the portal vein, as this exposes the graft directly to blood-and liver-mediated reactions [3,11,[16][17][18].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Currently, extensive islet cell significant after correction. death occurs in the immediate posttransplantation period (2,3,10,11), as well as a functional impairment in the RESULTS surviving endocrine cells (16,21).Our previous studies have shown that heterotopically implanted islets become The YC-3.0 islets retained their EYFP expression and remained at least 6 months after intrapancreatic transpoorly revascularized. Similar results were obtained irrespective of whether the islets were implanted beneath plantation (two out of two animals).…”
Section: Introductionmentioning
confidence: 99%
“…Remaining native pancreatic islets do not seem to interfere with the ulated expansion of the remnant endothelial cell pool or strategies to overcome the barrier for ingrowth of host formation of new blood vessels in islet graft; the vascular density in the grafts is similar to that obtained in vessels into the endocrine tissue are clearly warranted. islets implanted to cure diabetic recipients (22 pression for key enzymes in β-cell metabolism (16).…”
Section: Introductionmentioning
confidence: 99%